The ammoniation of total mixed fiber with mineral organic supplementation in ration to increase beef cattle production - Imsya, A.; windusari, Y.; Riswandi, R. (Journal of the Indonesian Tropical Animal Agriculture, 2020)
The objective of this study was to evaluate the level of organic minerals and total mixed fiber ammoniation (TMFA) as basal feed on the performance of beef cattle. This study used the In Vivo technique and the experimental method using t-test. The t-test compares the best supplementation result on in vitro research and control treatment, each treatment got6 replications. The treatments tested were P1: 60% TMF ammoniation + 15% swamp legume without supplementation of organic minerals P2: 60% TMF ammoniation + 1.5 x Organic macrominerals (Ca, P, and S) NRC (2000) + 15% Swamp Legumes. The parameters measured in the in-vivo technique were nutrient digestibility consisting of dry and organic matters, crude protein, crude fiber, NDF, and ADF. The animal performance: ration and dry matter consumption, body weight gain and ration efficiency. The results showed that supplementation of minerals in rations with TMFA as basal feed had a significant effect (P<0.05) on nutrient digestibility (dry matter, organic matter, crude fiber, NDF, and ADF) and animal performance. The conclusion of this study was supplementation of organic macrominerals 1.5 x (Ca, P, and S) NRC (2000) in a ration with TMF ammoniation as basal feed can improve the beef cattle performance.